Flexible Electronics and Healthcare Applications - Wang, Zixian; Sun, Lin; Ni, Yao; Liu, Lu; Xu, Wentao (Frontiers in Nanotechnology, 2021)
Flexible electronics has attracted tremendous attention in recent years. The essential requirements for flexible electronics include excellent electrical properties, flexibility and stretchability. By introducing special structures or using flexible materials, electronic devices can be given excellent flexibility and stretchability. In this paper we review the realization of flexible electronics from the perspective of structural design strategies and materials; then, healthcare application of flexible electronic systems was introduced. Finally, a brief summary and outlook are presented.